Applicability Degree of Autism Spectrum Disorder Diagnostic Criteria of Diagnostic and Statistical Manual of Mental Disorders –the 5 the Edition (DSM V) on Children Enrolled in Autism Centers in Jordan - Al-Badarneh, Mohammad; Smadi, Jamil (European Scientific Journal, ESJ, 2016)
This study aims to investigate the applicability of the diagnostic criteria of autism spectrum disorder in the diagnostic and statistical manual of mental disorders, fifth edition (DSM V) on the children enrolled in selected autism centers in Jordan. To achieve the objectives of the study, the researchers applied the scale of the (DSM V) on the children with autism spectrum disorder. The scale consisted of (30) items distributed on two areas. The first area is a lasting impairment in the social communication and interaction. The second area includes behavioral patterns and definite, repetitive and stereotyped interests and activities. The validity and reliability were extracted and calculated using the re-test application method, which amounted to (88.0) as well as the internal consistency, which reached to (94.0). The scale was also applied on the study samples that were represented by (300) children through the responses of the (94) teachers regarding the children with autism spectrum disorder. The results showed that the applicability of the diagnostic criteria of the autism spectrum in the diagnostic and statistical manual of mental disorders, (DSM V) on the children was low by (36.3%) with total occurrences of (109) children who suffered from the autism spectrum disorder, and (63.7%) of children on whom the two criteria were not applicable with a total of 191 children.